Distribusi Otot, Lemak dan Tulang pada Karkas Kambing Jantan Peranakan Etawah yang Diberi Suntikan Clenbuterol (DISTRIBUTION OF MUSCLE, FAT AND BONE IN MALE ETAWAH CROSS BREED BUCKS TREATED WITH CLENBUTEROL) - Kiranadi, Bambang; Putra, Bramada Winiar (Jurnal Veteriner, 2013)
Twenty growing cross breed etawah buck had been treated with clenbuterol every two days. Threelevels of clenbuterol, 5, 10 and 20 ìg/kg BW were injected intramuscularly from the thigh side every twodays. The animals were slaughtered and cut into five pieces, thorax, fore limb, loin, flank and hind limb.The components of muscle and fat for each component were separated for fat, muscle and bones analysis.The purpose of the experiment was to investigate the claim that clenbuterol has an effect on carcassquality. It is expected that clenbuterol will affect fat mobilization through the mechanism of stimulusrespond . In this experiment clenbuterol does not affect fresh carcass weight and carcasss empty bodyweight. However clenbuterol has the effect on muscle carcass thigh, thorax and flank, indicating proteinformation in the carcass. Further studies showed that clenbuterol affected the reduction of subcutanousfat in thigh and flank. Intermuscular fat of the thorax was also affected by clenbuterol. Furthermoreclenbuterol reduced the bones weight. It can be concluded that clenbuterol works at specific area of thebody, mobilizing the fat and bones follow with protein synthesis.
Keywords: Clenbuterol carcass quality